Calibrating Databases - Fischhoff, Baruch; MacGregor, Donald (Journal of the American Society for Information Science and Technology, 1986)
Searching for information in a database usually involves a series of decisions, as one chooses among alternative places to look. Behavioral decision theory investigates the cognitive processes involved in decision making, with a special focus on those that may impede effective performance. Applying this perspective to information search yields a set of measures for characterizing performance with different databases and a set of hypotheses for predicting search difficulties. These measures are employed and these hypotheses are examined in the context of searching for information in a familiar database, the Statistical Abstract of the US. Questionnaires concerning the database were completed by 109 subjects. Results generally duplicated previous findings with other decision-making tasks and indicated ways to improve performance. For instance, it was found that subjects had unrealistic expectations regarding their ability to locate information quickly.